Harmonic Distortion in an Off-Grid Renewable Energy System with Different Loads - Hojabri, Mojgan; Soheilirad, M. S. (2014)

(untitled)
This paper is started by discussed and compare the structures of three linear controller namely PI, PID, PR and RC controllers in order to reach the control of renewable energy systems. And continue by implementation of a PID controller with PWM inverter for controlling a single phase off-grid renewable energy system. The analysis includes dynamic response, voltage harmonic distortion and current harmonic distortion for different resistive and inductive loads. The system is simulated using Matlab Simulink and simulation results demonstrate the different effects of renewable energy systems on voltage and current waveform with different loads.